PFOA remediation from kaolinite soil by electrokinetic process coupled with activated carbon/iron coated activated carbon - permeable reactive barrier - Ganbat, Namuun (2024)
This study applied electrokinetic (EK) in situ soil remediation for perfluorooctanoic acid (PFOA) removal from kaolinite soil. The kaolinite soil was spiked with 10 mg/kg PFOA for the EK treatment using Sodium Cholate bio-surfactant coupled with Activated Carbon (AC) or iron-coated Activated Carbon (FeAC) permeable reactive barrier (PRB). The study also evaluated the impact of AC and FeAC PRBs' position on the EK process performance. In the EK with the PRB in the middle section, PFOA removal from kaolinite was 52.35 % in the AC-EK tests and 59.55 % in the FeAC-EK. Experimental results showed the accumulation of PFOA near the cathode region in FeAC PRB tests, hypothesising that Fe from the PRB formed a complex with PFOA ions and transported it to the cathode region. Spent PRBs were regenerated with methanol for PFOA extraction and reuse in the EK experiments. Although FeAC PRB achieved better PFOA removal than AC PRB, the EK tests with regenerated AC-EK and FeAC-EK PRBs achieved 40.37 % and 20.62 % PFOA removal. For EK with FeAC PRB near the anode, PFOA removal was 21.96 %. Overall, using PRB in conjunction with the EK process can further enhance the removal efficiency. This concept could be applied to enhance the removal of various PFAS compounds from contaminated soils by combining a suitable PRB with the EK process. It also emphasizes the feasibility of in-situ soil remediation technologies for forever chemical treatment.